PENGARUH SUHU PEMANASAN PADA STASIUN KERNEL SILO DRYER TERHADAP MUTU KERNEL DI PABRIK KELAPA SAWIT PT. XYZ - Zakwan; Mahyunis; Faisal, Busrizal; Sembiring, Arifa Sura; Noor, Faiz (Jurnal Agro Fabrica, 2024)
Oil palm plantations are widespread in Indonesia, triggering the birth of many palm oil processing industries, so that this plant becomes a commodity for the country. Palm oil factories process fresh fruit bunches (FFB) which will later produce crude palm oil (CPO) and palm kernel oil (PKO) as derivative products. Based on my experience and information, kernel processing in PKS cannot be fully maximized. Because many kernels are heated for a very long time so that the cost of production is high, and also many kernels are abandoned, moldy and smell rancid because the quality of the kernel is not fully achieved. In this case, the best processing of the kernel is needed. So that the quality of the kernel can be achieved. In this final assignment, it will be analyzed how the quality of the kernel is if heated with time and temperature below previous research. So that the kernel quality will be obtained according to SNI 01-000201- 1987 with lower energy consumption. This study will use a non-factorial random design method because it only has 1 factor, namely temperature variation (70 OC, 80 OC, and 100 OC).